Reading India now : contemporary formations in literature and popular culture - Ulka Anjaria (Black swan private limited, 2019)
"This project looks at the idea of the contemporary in 21st-century Indian literature and popular culture, working with a diverse archive that includes literary novels, commercial romances, nonfiction city writing, Hindi popular cinema, a television talk show, and the mixed media texts of a prominent feminist filmmaker"--